The Relationship between Policy Government and Retirement Stigma with Psychosocial Adaptation among Elderly in Jombang Regency - Siswati Siswati; Merryana Merryana; Retno Indarwati (Alta Dharma Publisher, 2020)
Introduction: The psycho-social adaptation of the elderly in retirement is influenced by several factors, including government policies and pension stigma received by the elderly from the surrounding community. Objective: This study aims to identify the relationship between government policy and pension stigma with elderly psychosocial adaptation in Jombang Regency. Methods: Type of quantitative research with the cross-sectional method. The sample in this study was 170 elderly in Jombang Regency obtained by using simple random sampling. The independent variable is government policy and pension stigma while the dependent variable is a psychosocial adaptation. Time of study starting March 13 - April 12, 2019. Result: The results of the study that government policies, pension stigma, and social adaptation were mostly sufficient. The chi-square test results of the relationship between government policy and psychosocial adaptation obtained p-value (0.045) <? (0.05). It means there is a meaningful relationship between government policies and retirement psychosocial adaptation in the elderly. The chi-square test results of the relationship between retirement stigma and psychosocial adaptation obtained p-value (0,000) <? (0.05). It means that there is a significant relationship between retirement stigma and retirement psychosocial adaptation in the elderly. Discussion: Government policy in preparing retired employees is needed through a holistic approach by considering the individual aspects of employees to help plan towards a happy retirement. The community can provide support by removing the stigma that has been believed so far that the elderly are no longer productive so they are dismissed from work.